Implementasi Supervisi Klinis dengan Pendekatan Contextual Teaching and Learning (CTL) di SDN 02 Kota Mukomuko Untuk Meningkatkan Kemampuan Guru dan Mutu pembelajaran Siswa - Mulkaziah Mulkaziah (Institut Agama Islam Negeri Bengkulu, 2020)
The continuous learning process makes the entire academic community feel at the saturation point. As a result, teachers undergo their teaching activities efficiently, students are not optimal in improving learning outcomes and active learning. Therefore we need special treatment in the form of clinical supervision with a Contextual Teaching and Learning approach in undergoing learning activities of teachers. The research method used in this research is school action research. The scope of this method is broader than in classroom action research, because it covers one school instead of just one class. The results showed that clinical supervision succeeded in increasing the average teacher performance. The increase was 11% -17% from cycle 1 to cycle 2. So clinical supervision is needed to improve teacher performance.